2022
DOI: 10.1021/jacs.2c06626
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Membrane Platform for the Visualization of Water Impermeability across the Liquid-Ordered Phase under Hypertonic Conditions

Abstract: Passive water penetration across the cell membrane by osmotic diffusion is essential for the homeostasis of cell volume, in addition to the protein-assisted active transportation of water. Since membrane components can regulate water permeability, controlling compositional variation during the volume regulatory process is a prerequisite for investigating the underlying mechanisms of water permeation and related membrane dynamics. However, the lack of a viable in vitro membrane platform in hypertonic solutions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…These characteristics reduce water permeability. In line with these findings, molecular dynamics (MD) simulations indicated that the presence of cholesterol in the 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphatidylcholine (POPC) bilayer[6], 1,2-dipalmitoyl-sn-glycero-3-phosphatidylcholine (DPPC) bilayer[7], phosphatidylglycerol bilayer[8] and dioleylphosphatidylcholine (DOPC)/ sphingomyelin bilayer[9] significantly reduced water permeability, demonstrating that reduced water permeability was caused by the increased organization of lipids in the presence of cholesterol.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…These characteristics reduce water permeability. In line with these findings, molecular dynamics (MD) simulations indicated that the presence of cholesterol in the 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphatidylcholine (POPC) bilayer[6], 1,2-dipalmitoyl-sn-glycero-3-phosphatidylcholine (DPPC) bilayer[7], phosphatidylglycerol bilayer[8] and dioleylphosphatidylcholine (DOPC)/ sphingomyelin bilayer[9] significantly reduced water permeability, demonstrating that reduced water permeability was caused by the increased organization of lipids in the presence of cholesterol.…”
Section: Introductionmentioning
confidence: 97%
“…phosphatidylglycerol bilayer [8] and dioleylphosphatidylcholine (DOPC)/ sphingomyelin bilayer [9] significantly reduced water permeability, demonstrating that reduced water permeability was caused by the increased organization of lipids in the presence of cholesterol.…”
Section: Introductionmentioning
confidence: 99%
“…In mixtures containing cholesterol that exhibit phase separation into liquid ordered (L o ) and liquid disordered (L d ) phases, the L o phase has lower water permeability. , However, the difference in water permeability between L o and L d is significantly lower than the difference between the permeability of gel and fluid phases of single-component lipid membranes. This difference is attributed to a permeation pathway that includes diffusion into the L d regions at the L o /L d boundary with subsequent diffusion along the membrane midplane …”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics simulation (MD) is a widely used method to get the molecular level understanding of the cation-membrane interaction at physiological conditions or osmotic pressures. As metal ions mainly interact with the outer membrane of RBCs, we constructed model membranes by 1,2-dioleoylsn-glycerol-3-phosphocholine (DOPC), which is one of the most abundant PC in the outer leaflet of the cell membrane of RBCs. , Using the CHARMM-GUI program, we designed four simulation systems, each consisting of 128 DOPC molecules (and about 6000 water molecules) with different metal ions: K­(I), Ca­(II), Zn­(II), or no metal ions (DOPC with water only). Figure c shows a typical snapshot of the system with Zn­(II), and the others are shown in Figure S14.…”
mentioning
confidence: 99%